Emergence of aortic aneurysms due to failure of adhesive bonds between proteoglycans. Issue 1 (15th March 2018) - Hillgärtner, Markus; Linka, Kevin; Itskov, Mikhail
Abstract: Aortic aneurysms are a common disease among older patients. Aneurysm ruptures cause more than 150 000 deaths annually [2]. One of the main risk factors which lead to the abnormal enlargements of vessels (>150% of original size) is arterial hypertension. This contribution presents a modeling approach, where the cyclic loading of the artery caused by the blood pressure leads to fatigue inside the arterial wall. The arterial wall is considered as a composite material, where a matrix (ground substance) is reinforced by collagen fibers consisting of fibrils connected by proteoglycan (PG) bridges. These PG bridges support interfibrillar sliding leading to lower fibril stretch [6]. Molecular adhesive bonds rupture under any pulling force if the force is held sufficiently long enough [1]. This rupturing over time leads to a decrease in the density of PG bridges, higher stretches in the fibrils, more damage inside the fibrils and finally to fatigue of the soft tissue which causes the abnormal enlargement. Finally the model is compared against experimental data of uniaxial tension tests and used in a FEM simulation to study the emergence of aortic aneurysms under arterial hypertension. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)